2020
DOI: 10.3389/fonc.2020.570656
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Deoxyguanosine Kinase Regulates NAD+ Biogenesis Independent of Mitochondria Complex I Activity

Abstract: Overexpression of DGUOK promotes mitochondria oxidative phosphorylation and lung adenocarcinoma progression. However, the role and mechanism of DGUOK in regulation of mitochondria function and lung cancer progression still poorly understood. Here we demonstrated that DGUOK regulated NAD+ biogenesis. Depletion of the DGUOK significantly decreased NAD+ level. Furthermore, knockout of the DGUOK considerably reduced expression of the NMNAT2, a key molecule controlling NAD+ synthesis, at both mRNA and protein level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…In our previous studies, we found that DGUOK deletion affected the assembly of mitochondrial complex I, and robustly inhibited lung adenocarcinoma tumor growth, metastasis, and CSC self-renewal (33,34). We also found DGUOK regulates nicotinamide adenine dinucleotide (NAD + ) biosynthesis independent of the mitochondrial complex I (35) that Dguok deficiency-mediated mitochondria dysfunction plays a key role in aging, which is consistent with previous research (36).…”
Section: Real-time Pcr Analysessupporting
confidence: 88%
See 1 more Smart Citation
“…In our previous studies, we found that DGUOK deletion affected the assembly of mitochondrial complex I, and robustly inhibited lung adenocarcinoma tumor growth, metastasis, and CSC self-renewal (33,34). We also found DGUOK regulates nicotinamide adenine dinucleotide (NAD + ) biosynthesis independent of the mitochondrial complex I (35) that Dguok deficiency-mediated mitochondria dysfunction plays a key role in aging, which is consistent with previous research (36).…”
Section: Real-time Pcr Analysessupporting
confidence: 88%
“…In our previous studies, we found that DGUOK deletion affected the assembly of mitochondrial complex I, and robustly inhibited lung adenocarcinoma tumor growth, metastasis, and CSC self-renewal(33, 34). We also found DGUOK regulates nicotinamide adenine dinucleotide (NAD + ) biosynthesis independent of the mitochondrial complex I (35). To further investigate the pathophysiological function of DGUOK, we constructed Dguok knockout mice (Fig S1A), in which the second exon of Dguok was completely deleted., and the deletion of which resulted in frame-shift mutation and early termination of translation.…”
Section: Resultsmentioning
confidence: 94%
“…Increased levels of CXCL14 mRNA have been detected in LUAD biopsies with a micropapillary pattern [ 55 ], and smoking-induced CXCL14 expression in the human airway epithelium has been implicated in chronic obstructive pulmonary disease (COPD)-mediated lung cancer development [ 56 ]. Similarly, NMNAT2 expression was found to be increased in LUAD specimens and correlated negatively with OS of patients, whereas the DGUOK-NMNAT2-NAD+ axis was suggested as a potential therapeutic target for the disease [ 57 ]. Increased expression levels of HLF, shown to promote cell-cycle progression in various cancers [ 58 ], ITGA2 , MUC1 , and DPY19L1 have also been proposed to confer prognostic value for the survival of patients suffering from LUAD malignancies [ 59 , 60 , 61 , 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, this osteosarcoma cell line also showed an upregulated NMNAT1 expression in response to DNA damage [108]. Lung adenocarcinoma shows high expression levels of NMNAT2, and the expression of this gene in this type of cancer was found to negatively correlate with patient survival in two different databases [114]. In lung cancer, NMNAT2 expression was shown to be regulated by deoxyguanosine kinase (DGUOK), a critical enzyme for mitochondrial purine metabolism [114].…”
Section: Nmnat As a Target In Cancermentioning
confidence: 98%